A coming attraction digital cinema. - Lubell, P.D.
Discusses the advent of the digital cinema where the film to be shown has been digitally recorded and stored on disk drives that have been brought to the theater, where it will be digitally projected as well. The author pays particular attention to digital projection methods
Keywords: Cinema program delivery; Digital cinema; Digital projection methods; Disk drives; Film